2012
DOI: 10.1080/08927014.2012.688957
|View full text |Cite
|
Sign up to set email alerts
|

Pioneer marine biofilms on artificial surfaces including antifouling coatings immersed in two contrasting French Mediterranean coast sites

Abstract: Marine biofilm communities that developed on artificial substrata were investigated using molecular and microscopic approaches. Polystyrene, Teflon® and four antifouling (AF) paints were immersed for 2 weeks at two contrasting sites near Toulon on the French Mediterranean coast (Toulon military harbour and the natural protected area of Porquerolles Island). Biofilms comprising bacteria and diatoms were detected on all the coatings. The population structure as well as the densities of the microorganisms differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 48 publications
5
75
2
1
Order By: Relevance
“…Our results indicated that the amount of bacteria on the surfaces from the control system was 10 8 cells·cm −2 . Similar numbers of bacterial microfouling have been reported on anti-fouling surfaces in oceanic waters, also in much warmer sites [24][25][26]. Hypochlorite treatment reduced the bacterial numbers by 10-1000-fold, but the efficiency depended on the coating.…”
Section: Discussionsupporting
confidence: 51%
“…Our results indicated that the amount of bacteria on the surfaces from the control system was 10 8 cells·cm −2 . Similar numbers of bacterial microfouling have been reported on anti-fouling surfaces in oceanic waters, also in much warmer sites [24][25][26]. Hypochlorite treatment reduced the bacterial numbers by 10-1000-fold, but the efficiency depended on the coating.…”
Section: Discussionsupporting
confidence: 51%
“…This technique has been used for counting bacteria in different environmental samples including soils, brackish waters, pond and lake waters, seawater, marine intertidal sediments, natural biofilms and even oyster tissue homogenates (Table A1). Previous studies on marine biofilms developing on surfaces submerged in the sea reported the use of scalpels to remove the biofilm from the substratum prior to enumeration on membrane filters [8][9][10][11][12]. Few studies reported the use of microscope slides to develop a biofilm and consequently enumerate bacteria in their native, hydrated conditions [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms can lead to corrosion of metals by increasing the open circuit potential toward positive values by metal deposition at the cathode, oxygen removal and acid production (Videla & Herrera 2005;Landousli et al 2011). While biocidal and foulingrelease coatings are generally free from macrofouling, they are still subject to colonisation by biofilms (Cassé & Swain 2006;Molino et al 2009;Dobretsov & Thomason 2011;Zargiel et al 2011;Briand et al 2012). Biofilms on antifouling (AF) coatings increase roughness and hence drag, which results in increased fuel consumption of vessels (Yebra et al 2006;Schultz et al 2011).…”
Section: Introductionmentioning
confidence: 99%